#TITLE_ALTERNATIVE# - FADLILAH RACHMAT (NIM 10204054), RIZKI
Linear accelerator is one of External Beam Radiotherapy (EBRT) equipment. Input for software to operate linear accelerator is the number of Monitor Unit (MU). Calculation of the number of Monitor Unit in division Treatment Planning System Rumah Sakit Hasan Sadikin Bandung was done by using software ISIS. Having accurate calculation of the number of Monitor Unit it is very important. Because of that, this final project has studied another method to calculate the number of Monitor Unit, i. e. Monte Carlo simulation. And then, we compare the number of Monitor Unit from software ISIS and from Monte Carlo simulation. Their standard deviations were (1-6)% for seven open fields of sizes (5x5)cm2, (7x7)cm2, (10x10)cm2, (15x15)cm2, (20x20)cm2, (24x24)cm2, (27x27)cm2, and the standard deviations decreased with the increased field of sizes. In comparison to the ISIS, the number of Monitor Unit from Monte Carlo simulation is bigger. This is caused by Monte Carlo simulation concepts that is probability of interaction from every Foton particle, however software ISIS uses radiation exposure geometry concept, so that Monte Carlo simulations are more accurate.